Sleeping with the enemy: Dichotomies and polarisation in Indian policy debates on the environmental and social effects of irrigation - Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2005)
Large-scale, government-managed canal irrigation represents the technocratic approach to water development. Large-scale irrigation faces many problems but they have been relegated to the periphery in the water debate generally and about large dams in particular. It has given rise to dichotomous thinking and polarised politics. This paper explores these issues in case of large canal irrigation in India. The debates imply implication for institutions, science and technology and developmental practices which need to be viewed within the domain of new approach.
urn:nbn:de:0202-20080911116
Keywords: 330